Peningkatan Kompetensi dan Pelatihan Guru dalam Pengabdian di Dunia Pendidikan - Muji Muji; Muhammad Saharudin; Muhammad Kibar; Syahrul Basirun (CV. ALIM'SPUBLISHING, 2026)
In the digital era, teachers are required to be creative in integrating technology with learning to make the learning process more engaging and effective. This study explores how the Wordwall application can bridge the gap between Islamic Religious Education (PAI) material, which is rich in moral values, and Physical Education, Sports, and Health (PJOK), which emphasizes the importance of physical health. This application provides interactive games that allow students to learn while playing, so that they not only understand religious teachings and physical skills but also experience a fun learning experience. Through various types of games such as puzzles and quizzes, students can more easily remember the lesson material and apply that knowledge in their daily lives. In addition, the use of Wordwall encourages active student participation in each learning session. This strengthens their engagement in the learning process and increases motivation to learn. The research findings show that Wordwall can transform the classroom atmosphere to be more lively, interactive, and collaborative, creating an environment that supports active and enjoyable learning for students.